Updates on Rabies virus disease: is evolution toward “Zombie virus” a tangible threat? Updates on Rabies virus disease - Lippi, Giuseppe; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2021)
Human rabies disease is caused by Rabies Lyssavirus, a virus belonging to Rhabdoviridae family. The more frequent means of contagion is through bites of infected mammals (especially dogs, but also bats, skunks, foxes, raccoons and wolves) which, lacerating the skin, directly inoculate virus-laden saliva into the underlying tissues. Immediately after inoculation, the Rabies virus enters neural axons and migrates along peripheral nerves towards the central nervous system, where it preferentially localizes and injuries neurons of brainstem, thalamus, basal ganglia and spinal cord. After an initial prodromic period, the infection evolves towards two distinct clinical entities, encompassing encephalitic (i.e., “furious”; ~70-80% of cases) and paralytic (i.e., “dumb”; ~20-30% of cases) rabies disease. The former subtype is characterized by fever, hyperactivity, hydrophobia, hypersalivation, deteriorated consciousness, phobic or inspiratory spasms, autonomic stimulation, irritability, up to aggressive behaviours. The current worldwide incidence and mortality of rabies disease are estimated at 0.175×100,000 and 0.153×100,000, respectively. The incidence is higher in Africa and South-East Asia, nearly double in men than in women, with a higher peak in childhood. Mortality remains as high as ~90%. Since patients with encephalitic rabies remind the traditional image of “Zombies”, we need to think out-of-the-box, in that apocalyptic epidemics of mutated Rabies virus may be seen as an imaginable menace for mankind. This would be theoretically possible by either natural or artificial virus engineering, producing viral strains characterized by facilitated human-to-human transmission, faster incubation, enhanced neurotoxicity and predisposition towards developing highly aggressive behaviours.